Hydroxyapatite-reinforced chitosan film on PEO-treated aluminum alloys for enhanced corrosion resistance - Yang Li; Shuyan Yang; Yong Wan (Journal of Materials Research and Technology)
Corrosion of aluminum alloys is a critical limitation in marine and engineering environments, necessitating multifunctional protective coatings. This study aimed to enhance corrosion resistance by incorporating hydroxyapatite (HAP) nanoparticles into chitosan (CS) films deposited on plasma electrolytic oxidation (PEO)-treated aluminum surfaces. The composite coatings were constructed by depositing HAP-reinforced chitosan films onto PEO-pretreated aluminum alloy via a dipping–pulling process. Comprehensive characterization—including spectroscopic, microscopic, electrochemical, and computational techniques such as FTIR and molecular dynamics (MD) simulations—was conducted to evaluate their structure and performance. Results show that HAP enhances hydrogen bonding with CS, forming a denser molecular network that seals micro-pores in the PEO layer. The modified coatings exhibited markedly improved properties, with surface hardness increasing from 203.7 MPa to 509.5 MPa and elastic modulus from 6.6 GPa to 17.8 GPa. Electrochemical tests revealed a reduction in corrosion current density (jcorr) from 1.12 × 10−7 to 5.26 × 10−9 A/cm2, along with a significant increase in polarization resistance (Rp) to 1.74 × 1010 Ω cm2. These findings demonstrate that HAP-reinforced CS films can significantly improve both the mechanical robustness and corrosion protection of PEO coatings on aluminum alloys.